The best interpolation method for wind speed by using GIS - Siti Nur’aisyah, Jamalludin (2019)
The wind speed had played the very vital role in weather forest because wind hazard damages increased every year. When estimating the wind speed is important to use the interpolation method especially the location do not has a weather forest or meteorological stations. In this research, the three different method of spatial interpolation which was Inverse Distance Weighting (IDW), Spline and Kriging were compared to determine the suitability for estimating wind speed. Therefore, the all methods were evaluated with the regression analysis and correlation coefficient analysis. Based on the results obtained, Kriging was shown the more suitable to estimate the wind speed by followed the other methods which are IDW and Spline. Future studies with more data collected, denser sample points and different cases can be carried out to obtain a more accurate result.